Carbohydrate Stabilized Ceramic Nanoparticles for the Delivery of a Poorly Soluble Drug, Lornoxicam - Vengala, Dr. Pavani (Asian Journal of Pharmaceutics (AJP), 2017)
Introduction: To enhance the delivery of poorly-soluble drugs, we have explored aquasomes (three-layered, ceramic core based, and oligosaccharide-coated nanoparticles) as potential carriers for the delivery of model hydrophobic drug lornoxicam (log P = 3.15). Materials and Methods: Ceramic nanoparticles were prepared using coprecipitation by sonication method. Cellobiose was used for coating onto ceramic core followed by loading of the lornoxicam by partial adsorption mechanism. The prepared system was characterized for size, shape, drug loading efficiency, and in vitro release profile (both 0.1 N hydrochloric acid solution and phosphate buffer solution, pH 6.8). Colorimetric analysis of sugar coating was done using phenol sulfuric acid method. Results and Discussion: The formed particles were spherical with an average particle size in the range of 60-300 nm, with a media of 87 nm. The in vitro dissolution performance was compared with that of pure drug and better results were observed. The cumulative lornoxicam release for the aquasome formulation (49%) was found to be higher than that of pure drug (34%) and was found to be gradual and linear in acidic media. Whereas, in phosphate buffer solution, pH 6.8, an incomplete release was observed with the pure drug (51% in 2 h) and 95% release was observed within 90 min from the formulation. Conclusion: Ceramic nanoparticles can be used for the enhancement of dissolution profile of poorly soluble drugs.